Chromosome Number Increasing in Torenia Hybrid by Application of Colchicine Tablet - Ragasova, Lucia; Ondrasek, Ivo; Taychasinpitak, Thunya; Pinthong, Suthasinee; Pensuriya, Banthita; Suwanseree, Valerie Web; Kikuchi, Shinji; Chanchula, Nattapong (Thai Journal of Science and Technology, 2016)
Abstract The effects of colchicine tablets on Torenia hybrids (Torenia fournieri x Torenia asiatica) were studied. Nodes and leaf sections were cut and soaked in 15 ppm concentration of colchicine solution for 0, 12, 24, 48 and 72 hours. The highest frequency of polyploid induction was 25% at the soaking duration of 48 hours. The results showed that the plants regenerated from the colchicine-treated explants displayed some of the morphological characteristics of polyploids, such as thick stems and shorter plant height. Keywords: tetraploid; polyploid; ornamental; mutation